Pendidikan Islam dan Teknologi Digital dalam Mendukung Teory Taxonomy Bloom - Ridwan, Ridwan (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
Digital technology plays an important role for the 21st century in helping human activities with the type and kinds of works. In Islamic terminology, the technological advancement as a platform for everyone to pay